Is retirement good or bad for mental and physical health functioning? Whitehall II longitudinal study of civil servants. Issue 1 (1st January 2003) - Mein, G; Martikainen, P; Hemingway, H; Stansfeld, S; Marmot, M
Abstract : Background: To determine whether retirement at age 60 is associated with improvement or deterioration in mental and physical health, when analysed by occupational grade and gender. Methods: Longitudinal study of civil servants aged 54 to 59 years at baseline, comparing changes in SF-36 health functioning in retired (n=392) and working (n=618) participants at follow up. Data were collected from self completed questionnaires. Results: Mental health functioning deteriorated among those who continued to work, but improved among the retired. However, improvements in mental health were restricted to those in higher employment grades. Physical functioning declined in both working and retired civil servants. Conclusion: The study found that retirement at age 60 had no effects on physical health functioning and, if anything, was associated with an improvement in mental health, particularly among high socioeconomic status groups.